FP2-3 Ten years of paediatric neuro-oncology surgery: quantifying and predicting complications after surgery for intracranial tumour excision. Issue 3 (14th February 2019) - Foster, MT; Grayston, R; Hennigan, D; Harishchandra, LS; Tonder, LV; Millward, CP; Pettorini, B; Sinha, A; Parks, C; Burn, S; Pizer, B; Mallucci, C
Abstract : Objectives: To measure complications of paediatric neurooncology surgery using the Clavien Dindo grading scale, and identify predictors of surgical morbidity. Design: Retrospective review of prospectively collected data. Subjects: All paediatric patients treated with craniotomy for excision of intracranial tumour between 2008 and 2017 in a single tertiary paediatric neurosurgery centre. Methods: Demographics, surgical details and perioperative complications were prospectively recorded between 0 and 30 days post operatively. These were retrospectively graded using the CD scale. Data analysis was done in R using logistic regression. Significance was defined as p<0.05 Results: Between 3/1/2008 and 21/12/2017 there were 322 operations, on 254 patients (142 Male). Median age at surgery was 9 years (IQR 4–13 years). 48% were without complication on the CD scale. Maximum CD grade complication for each procedure was 1 in 11%, 2 in 19%, 3A in 2%, 3B in 14%, and 4 in 0.6% of operations. 30 day mortality was 0.9%. CD grade of 3B or over was associated with infratentorial tumours (OR 2.24; CI 1.10–4.68; p=0.004) and WHO grade III tumours (OR 4.12; CI 1.56–10.86; p=0.028). Conclusions: Complications in paediatric neurooncology surgery are common overall, but our results are favourable in comparison to the literature. The CD scale has limitations in neurosurgery but gives insight into the health economic impact of complications. Infratentorial tumours, and WHO grade III tumours were associated with increased morbidity.